Ethical counselling and medical decision-making in the era of personalised medicine : a practice-oriented guide - Boniolo, Giovanni; Sanchini, Virginia (SpringerBriefs in applied sciences and technology. Ethical and legal issues in biomedicine and technology,, 2016)
This book offers an overview of the main questions arising when biomedical decision-making intersects ethical decision-making. It reports on two ethical decision-making methodologies, one addressing the patients, the other physicians. It shows how patients' autonomous choices can be empowered by increasing awareness of ethical deliberation, and at the same time it supports healthcare professionals in developing an ethical sensitivity, which they can apply in their daily practice. The book highlights the importance and relevance of practicing bioethics in the age of personalized medicine. It presents concrete cases studies dealing with cancer and genetic diseases, where difficult decisions need to be made by all the parties involved: patients, physicians and families. Decisions concern not only diagnostic procedures and treatments, but also moral values, religious beliefs and ways of seeing life and death, thus adding further layers of complexity to biomedical decision-making. This book, which is strongly rooted in the philosophical tradition, features non-directive counseling and patient-centeredness. It provides a concise yet comprehensive and practice-oriented guide to decision-making in modern healthcare.